Fine particulate pollution (Published for the United Nations by Pergamon, 1979)
Fine Particulate Pollution deals with the state of knowledge and the status of technology relating to pollution caused by fine particulates. The topics span all scientific and technical disciplines associated with atmospheric fine particulate pollution, including the definition of fine particulates, health effects, measurement, and sources, along with transport and transformation, control technology, regulations, economics, and research. This book is divided into six sections and begins with an overview of the chemical and physical characteristics of fine particles such as particle size, shape.